Kemampuan Koneksi Matematis Melalui Model Pembelajaran Connecting, Organizing, Reflecting, and Extending dan Means Ends Analysis - Nuri Dwi Indriani; Mega Achdisty Noordyana (Plusminus: Jurnal Pendidikan Matematika, 2021)
Kemampuan koneksi matematis siswarendah. Upaya meningkatkan kemampuan koneksi matematis siswa diantaranya dengan menerapkan model pembelajaran yang menekankan keaktifan siswa seperti Connecting, Organizing, Reflecting, and Extending (CORE) dan Means Ends Analysis (MEA). Penelitian bertujuan mengkaji perbedaan peningkatan kemampuan koneksi matematis siswa antara yang mendapatkan model pembelajaran CORE dengan MEA. Metode penelitian adalah kuasi eksperimen dengan populasi seluruh siswa kelas XI salah satu SMA Negeri di Garut. Sampel penelitian yaitu kelas XI MIPA 4 dan XI MIPA 5. Teknik pengumpulan data menggunakan tes uraian kemampuan koneksi matematis siswa. Hasil penelitian menunjukkan bahwa terdapat perbedaan peningkatan kemampuan koneksi matematis siswa antara yang mendapatkan model pembelajaran CORE dengan MEA, dengan kualitas peningkatan berinterpretasi sedang. Model pembelajaran CORE lebih baik dalam meningkatkan kemampuan koneksi matematis.The students' mathematical connection ability is low. Efforts to improve students' mathematical connection skills include applying learning models that emphasize student activity such as Connecting, Organizing, Reflecting, and Extending (CORE) and Means Ends Analysis (MEA). This study aims to examine the differences in the improvement of students' mathematical connection skills between those who received the CORE learning model and the MEA. The research method is quasi-experimental with a population of all students of class XI one of the Public SMA in Garut. The research sample is class XI MIPA 4 and XI MIPA 5. The data collection technique uses a description test of mathematical connection abilities and student attitude questionnaires. The results showed that there were differences in the improvement of students' mathematical connection skills between those who received the CORE and MEA learning models, with moderate improvement in interpreting quality. The CORE learning model is better at improving mathematical connection skills.